Acting on distances: A topology of accounting inscriptions. (May 2018) - Corvellec, Hervé; Ek, Richard; Zapata, Patrik; Zapata Campos, María José
Abstract: Following on the reiterated claim that accounting inscriptions make action at a distance possible, we draw on post-mathematical topology to explain that this distance work is dependent on inscriptions acting on distances. By adopting a relational understanding of space, we show that accounting inscriptions by themselves create the distances across which they operate. Our case study uses pay-as-you-throw solid waste-collection invoices in a new waste-collection program aimed at increasing the sustainability of waste management. By displaying weight and cost side by side, these invoices conduct topological operations that dissolve, create, and redefine the distance between people and their waste, between the economy and the environment, and between the city and its residents. The ability of these operations to mobilize a sense of environmental responsibility, enroll residents in the city's plans for sustainability, and translate political ambitions into individual behavior demonstrates that the performativity of accounting inscriptions resides in the efficacy of their distance work.